Floral trait similarity at the community‐level increases reproductive success suggesting facilitation through pollinator sharing - De Amorim, Marsal D. [UNESP]; Bergamo, Pedro J. [UNESP]; Thébault, Elisa; Perugini, Luís G. S.; Lopes, Sabrina A.; Rech, André R.; Maruyama, Pietro K. M. (Wiley, 2025)
The ability of plants to attract pollinators is context‐dependent, influenced by floral traits, abundance, and resources from the plant community. Indirect interactions through shared pollinators, from competition to facilitation, may lead to varied reproductive outputs in plants, and the mechanisms behind these interactions remain to be fully elucidated in complex ecological communities. We aimed to disentangle the mechanisms by which the floral community may impact pollinator sharing and plant reproductive success in the highly biodiverse Campo Rupestre from Brazil. To do so, we investigated the relationships among species traits, ecological networks, pollen deposition and reproductive output (seed set) in variable community contexts, using a piecewise structural equation modeling (SEM) approach. Plant species with similar flowers in relation to its community showed higher seed set, indicating facilitation. In contrast, species with high flower abundance showed decreased visitation rates per flower and conspecific pollen deposition, suggesting intraspecific competition. Our study reveals that, while there is an interplay between facilitation and competition, the former had a stronger influence on the reproductive output of plants sharing pollinators in a highly diverse tropical community. These results show that traits and abundance mediate complex indirect interactions in plant–pollinator communities.